Impaired Duration Perception in Patients With Unilateral Vestibulopathy During Whole-Body Rotation - Kwon, Eunjin; Lee, Ju-Young; Song, Jung-Mi; Kim, Hyo-Jung; Lee, Jong-Hee; Choi, Jeong-Yoon; Kim, Ji-Soo (Frontiers in Integrative Neuroscience, 2022)
This study aimed to evaluate vestibular perception in patients with unilateral vestibulopathy. We recruited 14 patients (9 women, mean age = 59.3 ± 14.3) with unilateral vestibulopathy during the subacute or chronic stage (disease duration = 6 days - 25 years). For the evaluation of position perception, the patients had to estimate the position after whole-body rotation in the yaw-plane. The velocity/acceleration perception was evaluated by acquiring patients’ decisions regarding which direction would be the faster rotation after a pair of ipsi- and contralesional rotations at various velocity/acceleration settings. The duration perception was assessed by collecting patients' decisions for longer rotation direction at each pair of ipsi- and contralesional rotations with various velocities and amplitudes. Patients with unilateral vestibulopathy showed position estimates and velocity/acceleration discriminations comparable to healthy controls. However, in duration discrimination, patients had a contralesional bias such that they had a longer duration perception for the healthy side during the equal duration and the same amplitude rotations. For the complex duration task, where a longer duration was assigned to a smaller rotation amplitude, the precision was significantly lower in the patient group than in the control group. These results indicate persistent impairments of duration perception in unilateral vestibulopathy and favor the vestibular system's intrinsic and distributed timing mechanism. Complex perceptual tasks may be helpful to disclose hidden perceptual disturbances in unilateral vestibular hypofunction.